2008
DOI: 10.1017/s1742170507002074
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of floating gardening in the north-eastern wetlands of Bangladesh for nutritional security and sustainable livelihood

Abstract: Floating gardening is a form of hydroponics or soil-less culture. It is an age-old practice of crop cultivation in the floodplains of southern Bangladesh, where aquatic plants such as water hyacinth (Eichhornia crassipes) are used to construct floating platforms on which seedlings are raised and vegetables and other crops cultivated in the rainy season. The platform residue is used in the preparation of beds for winter vegetable gardening. Floating gardening was introduced in 2006 on a pilot-scale in the north… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 11 publications
0
26
0
Order By: Relevance
“…The construction of floating gardens is a productivity intervention which has the potential to harness stagnant floodwater to culture vegetables (e.g., ginger, cowpea, eggplant, snake gourd) under hydroponic conditions. Large floating beds are constructed using aquatic flora, typically the prolific weed water hyacinth (Irfanullah et al 2008;Ullah et al 2009;Irfanullah et al 2011). Vegetable seedlings are subsequently transplanted from the homestead production system to the floating bed as monsoon floodwaters rise (Irfanullah et al 2008).…”
Section: Traditional Gher Improved Ghermentioning
confidence: 99%
“…The construction of floating gardens is a productivity intervention which has the potential to harness stagnant floodwater to culture vegetables (e.g., ginger, cowpea, eggplant, snake gourd) under hydroponic conditions. Large floating beds are constructed using aquatic flora, typically the prolific weed water hyacinth (Irfanullah et al 2008;Ullah et al 2009;Irfanullah et al 2011). Vegetable seedlings are subsequently transplanted from the homestead production system to the floating bed as monsoon floodwaters rise (Irfanullah et al 2008).…”
Section: Traditional Gher Improved Ghermentioning
confidence: 99%
“…The main floating agriculture practicing districts of Bangladesh are Barisal [18,42], Gopalganj [18,48,49] and Pirojpur [17,50]. Although, this technique were transferred to other flood prone areas of Bangladesh either extensively or some extent, like, Madaripur [39,45], Satkhira [17], Habiganj [51], Kishoreganj [19,52], Gaibandha [38,53], Khulna [54][55], Sunamganj [19,51,56], Netrokona [51,57], Faridpur [58], Lalmonirhat [59], and Jessore [40,[60][61]. At these regions, different types of monsoon and winter crops are grown.…”
Section: Farmers' Demographic Characteristicsmentioning
confidence: 99%
“…People who are practicing floating-bed cultivation are enjoying a better life economically, than those in other flood-affected areas who have not yet adopted this practice [21]. Through another study, Irfanullah et al [22] confirmed that floating cultivation practice helps to supplement people's income, which contributes towards the alleviation of poverty, and provides greater food security by increasing the landholding capacity of poor as well as landless people by allowing them to grow vegetables and crops with lower input costs, mainly due to the minimal infrastructure requirement. However, Chowdhury and Moore [23] chalked out the gap of field-based investigation as future research.…”
Section: Introductionmentioning
confidence: 99%
“…Both natural and artificial floating beds are used (John et al, 2009) for agriculture in many tropical wetlands of the world. Water hyacinth is the major ingredient of soilless cultivation (Irfanullah et al, 2008) to make floating bed locally known as dhap. Farmers make the bed as their desired size and shape.…”
Section: Introductionmentioning
confidence: 99%